2001
DOI: 10.1002/mrd.1126
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Xist expression begins at zygotic genome activation and is timed by a zygotic clock

Abstract: The imprinted mouse Xist (X-inactive specific transcript) gene is involved in the initiation of X-chromosome inactivation. Only the paternal Xist is expressed in preimplantation development beginning from the 4-cell stage, preceding and in correlation with paternal X-inactivation in the extraembryonic lineage of the blastocyst. To better understand the mechanisms regulating Xist expression in early development, we investigated the precise timing of its onset. We set up a single-cell RT-PCR for the simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…It would be of interest to examine whether these adjacent genes are also affected in female cells. We were also interested in whether Ftx is involved in the onset of the imprinted Xist upregulation during early preimplantation stages because previous studies have shown that Xist RNA upregulation is detected from the two- to four-cell stage onward1415. We used q-PCR to examine the Ftx expression at preimplantation stages and found that the expression begins at the blastocyst stage (Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…It would be of interest to examine whether these adjacent genes are also affected in female cells. We were also interested in whether Ftx is involved in the onset of the imprinted Xist upregulation during early preimplantation stages because previous studies have shown that Xist RNA upregulation is detected from the two- to four-cell stage onward1415. We used q-PCR to examine the Ftx expression at preimplantation stages and found that the expression begins at the blastocyst stage (Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…Single oocytes or PB in 0.5 µL PBS were transferred to the bottom of 0.5-mL thin-wall Eppendorf tubes containing 1.5 µL lysis buffer (0.8% Igepal, 1 U RNAsin/µL, 5 nM DTT) (24). The specimens were stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneous RNA extraction and cDNA synthesis Preimplantation embryos at blastocyst stages of development were transferred to Eppendorf tube containing 1.5 μl lysis buffer [33]. 2 μl random hexamer and 5 μl water was added to each 2 μl embryo sample.…”
Section: Measurement Of Intracellular Glutathione (Gsh) Levelmentioning
confidence: 99%